Species and Distribution of Shorebirds in Pattani Bay - Buatip, Somsak; Chantasuban, Tanakorn (Burapha Science Journal, 2026)
A study of species and distribution of shorebirds was conducted in 16 sites of Pattani Bay. Study habitats included salt marsh, mudflat, saltpan and water-coast. The shorebirds were counted by binoculars and a telescope from August 2017-July 2018. In this study, a total of 42 species were recorded: 24 species in Scolopacidae, 10 species in Charadriidae, 6 species in Laridae, 1 each in Rostratulidae and Recurvirostridae. Among the counted birds, 9 species were very common, 7 species common, 12 species uncommon and 14 species rare. The most widely distributed species was Common Sandpiper followed by Black-winged Stilt, Common Redshank, Common Greenshank, Marsh Sandpiper, Lesser Sand Plover and Whiskered Tern respectively. The habitat representing the highest number of species was the mudflat in Prince of Songkla University, followed by the Ban Rusamilae mudflat and Ban Bangplamo mudflat respectively. It also found that these areas harbored 3 endangered species (Far Eastern Curlew, Great Knot and Nordmann’s Greenshank), and 8 near-threatened species (Eurasian Curlew, Black-tailed Godwit, Bar-tailed Godwit, Asian Dowitcher, Red Knot, Rufous-necked Stint Curlew Sandpiper and Malaysian Plover)